2016
DOI: 10.15314/tjse.93545
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between core stability, dynamic balance and jumping performance in soccer players

Abstract: The purpose of this study was to investigate relationship between core stability, dynamic balance and jumping performance in soccer players. Seventeen male soccer players (mean ± SD: age, 21.06 ± 1.71 years) participated as volunteer in this study. Dynamic balance of the participants were evaluated at directions of anterior (A), posteromedial (PM) and posterolateral (PL) with Star Excursion Balance Test (SEBT). The core stability was evaluated with trunk flexion, side bridge, and trunk extension tests. For jum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 17 publications
(17 reference statements)
2
41
0
2
Order By: Relevance
“…The results of this study are consistent and in line with similar studies that have described the effects of core district training on vertical jumping and sprinting performances in young soccer players (Ozmen, 2016;Hoshikawa et al, 2013;Afyon, 2014) in gymnastic (Durall et al, 2009), in professional female futsal players (Lago-Fuentes et al, 2018) or in young basketball players (Sannicandro & Cofano, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study are consistent and in line with similar studies that have described the effects of core district training on vertical jumping and sprinting performances in young soccer players (Ozmen, 2016;Hoshikawa et al, 2013;Afyon, 2014) in gymnastic (Durall et al, 2009), in professional female futsal players (Lago-Fuentes et al, 2018) or in young basketball players (Sannicandro & Cofano, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…This results confirming the effectiveness of the core stability exercises to influence the speed and jump tests and the ES value underlines its size (Lago-Fuentes et al, 2018;Ozmen, 2016;Hoshikawa et al, 2013;Afyon, 2014).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Potentially, the execution of this test might require, among others, adequate levels of hip and knee strength, power, trunk or core stability, coordination and lower extremity ranges of motion (ROM). With the aim of improving the design of training interventions, some studies have explored the individual contribution of certain measures of knee strength [1517], hip strength [1719], lower extremity power [20], core stability [17] and lower extremity ROMs [17,21] on y-balance test performance using linear regression models in different cohorts of athletes. However, these studies have reported conflicting results that might not permit clinicians, physiotherapists and physical trainers to make general training recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Bazı çalışmalarda, denge ile sıçrama performansının ilişkisi incelenmiş ancak bu sonuçlar fiziksel aktivite düzeyi ile ilişkilendirmesi yapılmamıştır. [12][13][14][15] Çalışmamızın amacı, spor bilimleri fakültesinde lisans eğitimi alan amatör sporcularda denge, dikey sıçrama performansı ile fiziksel aktivite düzeyi arasındaki ilişkinin araştırılmasıdır.…”
unclassified